Psychological empowerment and challenge-oriented organizational citizenship behavior: a dual process model - Xu, Qingquan; Liu, Shan; Huang, Haishen (Frontiers in Psychology, 2024)
Encouraging proactive behavior among employees is a crucial pathway for companies to adapt swiftly and gain a competitive edge. In contrast to other forms of organizational citizenship behavior that tend to preserve existing work practices within the organization, Challenge-Oriented Organizational Citizenship Behavior (COCB) aims to improve upon these by offering constructive suggestions and altering employees' work methods, policies, and procedures for the benefit of the organization. However, not all employees are willing to engage in COCB, even when the organization actively encourages participation. Departing from traditional perspectives on workplace environments and leadership, we propose that psychological empowerment at the individual level may be a precursor to employees' engagement in COCB. Based on social exchange theory, this study examines how employees' psychological empowerment affects their challengeoriented organizational citizenship behavior (COCB), including the mediating roles of perceived insider status and affective commitment, as well as the moderating role of Chinese traditionality. Data was collected from 223 employees of manufacturing, IT, finance and service enterprises in Southern China using a multi-source and multi-wave survey. Results of the Structural Equation Modeling (SEM) show that psychological empowerment can positively affect COCB. Both perceived insider status and affective commitment act as mediators in the relationship between psychological empowerment and COCB. Moreover, Chinese traditionality has a moderating effect on the relationship between psychological empowerment and these mediators, and also the indirect effect of psychological empowerment on COCB. Specifically, the indirect effect was stronger when employees with lower levels of Chinese traditionality. This study provides a theoretical foundation for the individual-level antecedents of COCB, elucidating how the social exchange process between employees and the organization is transformed into COCB through psychological empowerment.